INTER-CARRIER INTERFERENCE REDUCTION TECHNIQUE IN OFDM SYSTEM BASED ON SELF CANCELLATION TECHNIQUE (International Journal of Engineering and Computer Science, 2012)
Orthogonal frequency division multiplexing (OFDM) is considered as a one of the best modulation schemes in wireless communications. However, OFDM suffers from the sensitivity to frequency offset. This frequency offset introduces the problem of inter-carrier interference (ICI) in OFDM system. This paper presents a new self cancellation technique (modified self cancellation technique) using the self cancellation technique with zero – gab. In proposed technique a zero sub-carriers carries are used in order to mitigate the interference occurred by the main – lobe of the two adjacent sub-carriers, in addition to zeros sub-carrier, the proposed technique used self-cancellation in order to mitigate the effect of the side-lobes of other sub-carriers. In terms of carrier-to-interference ratio (CIR) and bit-error rate (BER) the modified self cancellation technique gives good results compared to that using only the conventional self cancellation techniqu